2015
DOI: 10.1002/jbm.a.35540
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation, biocompatibility, and osteoconduction evaluation of collagen‐nanohydroxyapatite cryogels for bone tissue regeneration

Abstract: Designing biomimetic biomaterials inspired by the natural complex structure of bone and other hard tissues is still a challenge nowadays. The control of the biomineralization process onto biomaterials should be evaluated before clinical application. Aiming at bone regeneration applications, this work evaluated the in vitro biodegradation and interaction between human bone marrow stromal cells (HBMSC) cultured on different collagen/nanohydroxyapatite cryogels. Cell proliferation, differentiation, morphology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…Therefore, to reinforce the strength of the cryogel for compression or other types of stress and to increase biocompatibility and accelerate biomineralization of the cryogel, HA was introduced. Mechanical measurements showed that addition of HA significantly increased the elastic modulus of CHI-PVA-HA-Hep-GA cryogel (1085 ± 428 kPa) and that the value was significantly higher in comparison to other cryogel-based scaffolds designed for bone regeneration [43][44][45][46][47][48][49]. Degradation experiments confirmed a decreased in vitro degradation rate of HA-containing cryogels, which is in line with other published data [45,50].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, to reinforce the strength of the cryogel for compression or other types of stress and to increase biocompatibility and accelerate biomineralization of the cryogel, HA was introduced. Mechanical measurements showed that addition of HA significantly increased the elastic modulus of CHI-PVA-HA-Hep-GA cryogel (1085 ± 428 kPa) and that the value was significantly higher in comparison to other cryogel-based scaffolds designed for bone regeneration [43][44][45][46][47][48][49]. Degradation experiments confirmed a decreased in vitro degradation rate of HA-containing cryogels, which is in line with other published data [45,50].…”
Section: Discussionsupporting
confidence: 89%
“…In vitro: Differentiation of human bone marrow stromal cells into osteoblastic phenotype. In vivo: Reduced inflammatory response by new tissue production [72] Collagen-nanoHA biocomposite cryogels…”
Section: Scaffolds Outcome Referencementioning
confidence: 99%
“…Normal bone regeneration is a complex but well-orchestrated physiological process that includes the initiation of ossification, osteoinduction, and osteogenesis [6][7][8][9]. Specifically, when bone injury occurs, a series of signaling pathways is activated, which, in turn, leads to angiogenesis and other downstream events, and these together establish a favorable microenvironment, which set the stage for stem cell based fracture healing/regeneration [10].…”
Section: Introductionmentioning
confidence: 99%